2016
DOI: 10.1007/s13277-015-4618-1
|View full text |Cite
|
Sign up to set email alerts
|

p21 and CK2 interaction-mediated HDAC2 phosphorylation modulates KLF4 acetylation to regulate bladder cancer cell proliferation

Abstract: Krüppel-like factor 4 (KLF4) is a transcription factor involved in both tumor suppression and oncogenesis as a transcriptional activator or repressor in a context-dependent manner. KLF4 acts as a regulator of p53 depending on p21 status in breast cancer. However, the mechanisms underlying the distinct role of KLF4 remain poorly understood. Here, we revealed that p21 depletion converted KLF4 from a cell cycle inhibitor to a promoter of bladder cancer cell proliferation. Additionally, KLF4 was acetylated in a p2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Mammalian KLF4 suppresses keratinocyte proliferation by transcriptional activation of CDKN1A/p21 expression [35]. Nevertheless, some studies have shown that KLF4 can also facilitate cell proliferation [24, 36, 37]. For example, KLF4 plays an essential role in B cell development and in activation-induced B cell proliferation by regulating Cyclin D2 expression [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian KLF4 suppresses keratinocyte proliferation by transcriptional activation of CDKN1A/p21 expression [35]. Nevertheless, some studies have shown that KLF4 can also facilitate cell proliferation [24, 36, 37]. For example, KLF4 plays an essential role in B cell development and in activation-induced B cell proliferation by regulating Cyclin D2 expression [36].…”
Section: Discussionmentioning
confidence: 99%
“…For example, KLF4 plays an essential role in B cell development and in activation-induced B cell proliferation by regulating Cyclin D2 expression [36]. KLF4 also functions as an oncogene to promote proliferation of breast cancer and bladder cancer cells in the presence of RAS V12 -Cyclin-D1 signaling or the absence of p21 CIP1 [24, 37]. Altogether, our findings further support the idea that KLF4 may exert distinct functions to regulate stem cell proliferation in a context-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Among solid tumors, overexpression and/or important roles have been found for CK2 in glioblastoma, 94 – 98 medulloblastoma, 99 , 100 prostate cancers, 101 103 ovarian cancers, 104 107 breast cancers, 72 , 108 – 112 head and neck squamous cell cancers, 62 , 113 , 114 lung cancers, 113 , 115 – 117 melanoma, 118 , 119 renal cell carcinoma, 73 , 120 122 bladder cancers, 123 , 124 pancreatic cancers, 125 , 126 cholangiocarcinoma, 36 , 127 esophageal cancers, 128 , 129 gastric cancers, 130 133 hepatocellular carcinoma, 134 137 mesothelioma, 138 cervical cancers, 139 141 and other squamous cell carcinoma. 142 In this list, the references quote the first chronological evidence and the most relevant findings of CK2 overexpression or fundamental roles in the indicated type of tumor (not considering the many publications dealing with CK2 inhibitor treatment, unless conclusions highlighted specific CK2 functions in the treated tumor).…”
Section: Ck2 In Human Diseasesmentioning
confidence: 99%
“…Acetylation of KLF4 at lysine residues 225 and 229 mediated by the p300/CBP complex inhibits the ability of KLF4 to activate downstream targets (18). In urinary bladder cancer cells, p21/CK2 interaction enhances HDAC2 phosphorylation and restricts KLF4 deacetylation and subsequence tumor promotion (19). In contrast, overexpression of p300/CBP causes KLF4 acetylation and switches its activity to a tumor suppressor.…”
Section: Biochemical Activitiesmentioning
confidence: 99%